C-reactive protein and diabetic retinopathy in Chinese patients with type 2 diabetes mellitus - Xiu-Fen Yang (International Journal of Ophthalmology, 2016)
AIM: To investigate the relationship between C-reactive protein (CRP) and diabetic retinopathy (DR) in a cohort of Chinese patients with type 2 diabetes mellitus (T2DM). METHODS: Community-based observational cohort study. There were 1131 participants recruited from November 2009 to September 2011 in Desheng community in urban Beijing. Patients diagnosed T2DM were recruited and underwent a standardized evaluation consisting of a questionnaire, ocular and anthropometric examinations and laboratory investigation. The presence and severity of DR were assessed by seven fields 30° color fundus photographs. Subjects were then classified into groups with no DR, any DR, or vision-threatening DR. CRP was analyzed from serum of study subjects. RESULTS: A total of 1007 patients with T2DM were included for analysis, including 408 (40.5%) men and 599 (59.5%) women. The median CRP level was 1.5 mg/L for women and 1.1 mg/L for men (P=0.004, OR 0.37, 95% CI 0.18-0.74). After adjusting for possible covariates, higher levels of CRP were associated with lower prevalence of any DR (P=0.02, OR 0.55, 95% CI 0.35-0.89), but not associated with vision-threatening DR (P=0.62, OR 0.78, 95% CI 0.28-2.14). After stratification by sex, the inverse association between CRP and DR was found to be statistically significant in men (P=0.006, OR 0.35, 95% CI 0.16-0.73), but not in women (P=0.58, OR 0.88, 95% CI 0.29-1.16). CONCLUSION: The data drawn from a Chinese population with T2DM suggest that increasing CRP levels may be inversely associated with development of DR.